P420 Understanding PrEP service delivery preferences among black women in urban and rural counties in the US deep south. (14th July 2019) - Elopre, Latesha; Mcdavid, Chastity; Johnson, Bernadette; Gordon, Bretia; Pol, Barbara Van Der; Marrazzo, Jeanne; Mugavero, Michael
Abstract : Background: In the US, women account for approximately 20% of all new HIV infections, among which two-thirds are Black women. These health disparities are most pronounced in the Deep South. We conducted focus groups in urban and rural settings in Alabama to understand attitudes and preferences for PrEP service delivery among Black women. Methods: Our group members consisted of HIV-negative women between the ages of 16–65. Items and analyses were grounded in a conceptual framework using constructs from two behavioral models. Two coders independently conducted inductive and deductive thematic coding to determine major themes. Results: 25 rural (median age 44, 48% income <$25, 000, 36% Bachelor's degree) and 22 urban residents (median age 35, 14% income <$25, 000, 54% Bachelor's degree) were enrolled. Common themes identified among both groups of women were lack of awareness regarding PrEP and openness to utilization of PrEP if self-perceived risk for HIV was high. Among rural women, many expressed more overall distrust in knowing their partners risk of HIV infection as well as fear of potential disclosure if accessing PrEP within their community. Rural women also reported more concerns about stigma related to PrEP and structural barriers limiting access to service. Many rural women felt churches could be avenues to increase PrEP awareness. While urban women did not endorse the same concerns over where they would receive PrEP, they commonly reported concerns that PrEP would lead to increased "promiscuity" among its users. Conclusion: Black women in the Deep South had differing preferences regarding PrEP service delivery and messaging depending on whether they lived in urban or rural settings. These findings can inform targeted intervention development by emphasizing the need for partnerships with trusted community organizations and utilization of service delivery strategies that allow for anonymity to increase uptake of PrEP especially among rural Black women. Disclosure: No significant relationships.